Validation of modified dietary habits instrument in cardiovascular diseases study - Sajid, Mirza Rizwan; Noryanti, Muhammad; Roslinazairimah, Zakaria; Ahmad, Shahbaz (AIP Publishing, 2020)
The association between dietary habits and cardiovascular diseases (CVDs) has been established. However, the dietary habits vary among countries, therefore, there is scarcity in the literature for a standardized instrument to assess the dietary habits. This paper is aimed to evaluate the psychometric properties of modified dietary habits instrument, originally based on a food frequency questionnaire (FFQ). In this case-control study, it was used to find the most prevalent dietary habits in CVDs patients and their corresponding controls. The modified instrument consisted of 13 items representing thirteen food groups identified from CVDs related studies and FFQ. A sample of 180 (90 cases and 90 controls) was selected from the largest cardiac hospital of Pakistan through systematic sampling. Data was collected through modified instrument using direct investigation method. Twelve food groups were validated which further constituted two main factors labelled; healthy and unhealthy dietary habits. Exploratory factor analysis explained 70% and 68% variation through these two main identified dietary habits in cases and control, respectively. Internal consistency reliability for healthy and unhealthy dietary habits in cases were 0.905 and 0.879 and almost similar coefficient of reliability was recorded in the control group. Further, the mean score of healthy dietary habits was significantly less than unhealthy dietary habits (p<0.001) in the cases and vice versa in controls. This study concludes that the modified instrument is valid and reliable and should be used to assess the dietary habits in CVDs related studies. Further, mean score of unhealthy dietary habits can help in disease prediction models and early diagnosis of cardiac problems.